Black girls : migrant domestic workers and colonial legacies - Marchetti, Sabrina (Studies in global social history ;, 2014)
In today's Europe, migrant domestic workers are indispensable in supporting many households which, without their employment, would lack sufficient domestic and care labour. Black Girls collects and explores the stories of some of the first among these workers. They are the Afro-Surinamese and the Eritrean women who in the 1960s and 70s migrated to the former colonising country, the Netherlands and Italy respectively, and there became domestic and care workers. Sabrina Marchetti analyses the narratives of some of these women in order to powerfully demonstrate how the legacies of the colonial past have been, at the same time, both their tool of resistance and the reason for their subordination.